2016
DOI: 10.1002/rcm.7501
|View full text |Cite
|
Sign up to set email alerts
|

Measuring 210Pb by accelerator mass spectrometry: a study of isobaric interferences of 204,205,208Pb and 210Pb

Abstract: This study identified key interferences in the measurement of PbF3 (-) → Pb(3) (+) ions and demonstrated a new AMS method to measure (210) Pb. This new AMS technique is about five times more sensitive than gamma and beta spectroscopy measurements of (210) Pb and the measurement time is much shorter. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Together with their later work on isobaric interferences (Sookdeo et al . ), the authors demonstrated about five times better sensitivity than gamma and beta spectroscopy of 210 Pb and much shorter measurement times.…”
Section: Advances In Accelerator‐based Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Together with their later work on isobaric interferences (Sookdeo et al . ), the authors demonstrated about five times better sensitivity than gamma and beta spectroscopy of 210 Pb and much shorter measurement times.…”
Section: Advances In Accelerator‐based Methodsmentioning
confidence: 90%
“…Hence, Sookdeo et al (2015) investigated the effect of different target compositions on the strength and stability of 208 PbF À 3 currents and 210 Pb counts. Together with their later work on isobaric interferences (Sookdeo et al 2016), the authors demonstrated about five times better sensitivity than gamma and beta spectroscopy of 210 Pb and much shorter measurement times.…”
Section: Fundamental Research Devoted To Cosmogenic Radionuclidesmentioning
confidence: 93%
“…The possibility of employing AMS, using lead fluoride targets, to measure 210 Pb was first discussed about 20 years ago [15,16]. Most recently, the André E. Lalonde AMS Laboratory (AEL-AMS) has performed similar studies [17,18]. These have corroborated the observation that the extraction of (PbF 3 )ions from PbF 2 targets is a good choice, offering a good ionization efficiency [19,20].…”
Section: Introductionmentioning
confidence: 98%